2014
DOI: 10.1136/bcr-2014-205558
|View full text |Cite
|
Sign up to set email alerts
|

Complete axial torsion of pregnant uterus with leiomyoma

Abstract: Uterine torsion is defined as a rotation of the uterus of more than 45° along its long axis. It is a rare complication during pregnancy; a common cause of torsion can be uterine myoma. Here we describe the case of a 27-year-old G2P1+0 woman at 15 weeks 3 day pregnancy, who presented to our outpatient department as a case of acute abdomen, in a state of shock. Clinical findings did not correlate with investigation. On lapratomy she was diagnosed as a case of complete axial torsion of pregnant uterus with fundal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 10 publications
0
13
2
Order By: Relevance
“…On US, painful myoma >200 cm 3 presenting a change in the echogenicity with the appearance of internal cystic areas can suggest red degeneration and infarction . Low indices on 3‐D Doppler are associated with the ischemic processes within the tumor . MRI should be considered in such situations to confirm the diagnosis and facilitate fibroid mapping before surgery.…”
Section: Obstetric Complications Of Myomas During Pregnancymentioning
confidence: 99%
“…On US, painful myoma >200 cm 3 presenting a change in the echogenicity with the appearance of internal cystic areas can suggest red degeneration and infarction . Low indices on 3‐D Doppler are associated with the ischemic processes within the tumor . MRI should be considered in such situations to confirm the diagnosis and facilitate fibroid mapping before surgery.…”
Section: Obstetric Complications Of Myomas During Pregnancymentioning
confidence: 99%
“…Finally, 38 articles were included in the analysis. In our literature review, none UTs were reported in the first trimester of pregnancy, five (13%) cases [38][39][40][41][42] in the second trimester, and 33 (87%) cases occurred in the third trimester. Most of the cases concerned a singleton pregnancies and only four cases 6,9,30,37 (10.5%) a twin pregnancy.…”
Section: Literature Reviewmentioning
confidence: 75%
“…45 Some authors report possible morbidity with a posterior incision with increased risk of surgical bleeding and uterine rupture in following pregnancies. 13,24 In few cases, UT was suspected to reduce adnexal blood supply 38,40 simulating hence an adnexal torsion 46 and requiring salpingo-oophorectomy. 38 Bilateral salpingectomy could be also safely performed for sterilization without increasing complication rate.…”
Section: Discussionmentioning
confidence: 99%
“…The authors present a case of asymptomatic torsion with 180-degree levorotation of the uterus at the time of caesarean section. Diagnosis was made following delivery of the fetus and de torsion of the uterus to facilitate hemostasis of a bleeding vein in the IP vascular bundle [21,22]. This case report and review has been undertaken to reaffirm the awareness of uterine torsion among practitioners and provide an update of this rare obstetric condition.…”
Section: Discussionmentioning
confidence: 97%